2021
DOI: 10.3390/jcm10081787
|View full text |Cite
|
Sign up to set email alerts
|

Bidirectional Association between Metabolic Control in Type-2 Diabetes Mellitus and Periodontitis Inflammatory Burden: A Cross-Sectional Study in an Italian Population

Abstract: This study assessed the periodontal conditions of type 2 diabetes (T2DM) patients attending an Outpatient Center in North Italy and explored the associations between metabolic control and periodontitis. Periodontal health of 104 T2DM patients (61 men and 43 women, mean age of 65.3 ± 10.1 years) was assessed according to CDC/AAP periodontitis case definitions and Periodontal Inflamed Surface Area (PISA) Index. Data on sociodemographic factors, lifestyle behaviors, laboratory tests, and glycated hemoglobin (HbA1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
2
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 61 publications
0
18
2
3
Order By: Relevance
“…El deficiente control glucémico en los pacientes diabéticos conduce a una respuesta inflamatoria desregulada, la cual involucra la actividad inmunitaria, la función de los neutrófilos y el patrón de citoquinas, promoviendo el daño del tejido conectivo y produciendo en muchos casos inflamación de las encías, destrucción del periodonto y migración patológica de los dientes, con la consiguiente generación de diastemas, además de presentar un mayor sangrado gingival, en contraste con los pacientes diabéticos controlados, independientemente de los porcentajes de placa bacteriana registrados (Nascimento et al, 2018;AL-Haddad et al, 2021;Romano et al, 2021). En ese sentido, se ha evidenciado también que el riesgo de padecer periodontitis aumenta 2 a 3 veces en perso-nas con diabetes en contraste con aquellas no padecen dicha enfermedad y que el nivel glucémico es determinante para establecer el riesgo (Asthana & Chhina, 2021;Rapone et al, 2021).…”
Section: Resultsunclassified
“…El deficiente control glucémico en los pacientes diabéticos conduce a una respuesta inflamatoria desregulada, la cual involucra la actividad inmunitaria, la función de los neutrófilos y el patrón de citoquinas, promoviendo el daño del tejido conectivo y produciendo en muchos casos inflamación de las encías, destrucción del periodonto y migración patológica de los dientes, con la consiguiente generación de diastemas, además de presentar un mayor sangrado gingival, en contraste con los pacientes diabéticos controlados, independientemente de los porcentajes de placa bacteriana registrados (Nascimento et al, 2018;AL-Haddad et al, 2021;Romano et al, 2021). En ese sentido, se ha evidenciado también que el riesgo de padecer periodontitis aumenta 2 a 3 veces en perso-nas con diabetes en contraste con aquellas no padecen dicha enfermedad y que el nivel glucémico es determinante para establecer el riesgo (Asthana & Chhina, 2021;Rapone et al, 2021).…”
Section: Resultsunclassified
“…The increased risk of periodontitis in DM was first described by Löe in 1993, and periodontitis was found as the sixth complication of DM [ 18 ]. Since then several epidemiological studies have confirmed that patients with both type 1 and type 2 DM have a three- to fourfold increased risk of periodontitis and severity of periodontitis is much greater in uncontrolled DM [ 19 , 20 , 21 , 22 , 23 ]. Moreover, the American Academy of Periodontology (AAP) and the European Federation of Periodontology (EFP) added DM among the risk factors for the progression of periodontal disease [ 3 , 24 ] and recommend the use of HbA1c for periodontitis grading [ 3 ].…”
Section: Bidirectional Relationship Between Periodontitis and Dmmentioning
confidence: 99%
“…The implementation of this classification improved reporting quality and permitted meaningful comparisons of the prevalence of periodontal diseases across populations in epidemiological studies (48). Indeed, many recent epidemiological studies with diverse populations in different parts of the world have used this classification (52)(53)(54)(55)(56)(57), as well as (58)(59)(60)(61) and (61)(62)(63).…”
Section: Periodontitismentioning
confidence: 99%